Benjamin's 'flâneur' and serial murder: An ultra-realist literary case study of Levi Bellfield. (December 2019) - Lynes, Adam; Kelly, Craig; Uppal, Pravanjot Kapil Singh
This article seeks to develop criminological theory with the application of a literary device known as the 'flâneur' – an individual described as a 'stroller' – to serial murderer Levi Bellfield. With this application of the 'flâneur' to the phenomenon of serial murder, this article provides a fresh theoretical 'lens', and specifically sheds light on how particular serial murderers operate and evade detection in modern society. The importance of modernity to the phenomenon of serial murder is also considered utilizing Ultra-Realist theory, resulting in both a micro and macro examination into how the modern urban landscape has subsequently created an environment in which the serial killer both operates and comes to fruition. This synthesis between the application of literary devices, criminological theory and socio-cultural concepts not only raises important and previously neglected questions pertaining to serial murder, but also assists in forming the more sinister relative of the flâneur: the 'dark flâneur'.